2012
DOI: 10.1270/jsbbs.61.531
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and molecular bases of photoperiod responses of flowering in soybean

Abstract: Flowering is one of the most important processes involved in crop adaptation and productivity. A number of major genes and quantitative trait loci (QTLs) for flowering have been reported in soybean (Glycine max). These genes and QTLs interact with one another and with the environment to greatly influence not only flowering and maturity but also plant morphology, final yield, and stress tolerance. The information available on the soybean genome sequence and on the molecular bases of flowering in Arabidopsis wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
161
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(170 citation statements)
references
References 101 publications
3
161
1
5
Order By: Relevance
“…Group II consisted of landraces that are grown as a short-season crop across Japan and the Korean peninsula (9-15), including Sakamotowase, which has the genotype e3e3E4E4 and a dysfunctional allele (e1-fs) at the E1 locus [19][20][21]. Group III consisted of landraces collected in northern Honshu, Japan (16)(17)(18)(19)(20)(21). Tsukue-4 (group IV, accession 22) and Otomewase (group V, accession 23) together formed a loose clade.…”
Section: Classification Of Photoperiod-insensitive Soybean Accessionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Group II consisted of landraces that are grown as a short-season crop across Japan and the Korean peninsula (9-15), including Sakamotowase, which has the genotype e3e3E4E4 and a dysfunctional allele (e1-fs) at the E1 locus [19][20][21]. Group III consisted of landraces collected in northern Honshu, Japan (16)(17)(18)(19)(20)(21). Tsukue-4 (group IV, accession 22) and Otomewase (group V, accession 23) together formed a loose clade.…”
Section: Classification Of Photoperiod-insensitive Soybean Accessionsmentioning
confidence: 99%
“…The genetic mechanism of the photoperiod insensitivity varies among cultivars [16]. Genetic analyses have revealed that soybean cultivars and landraces that are adapted to the cool summers of northern Japan possess recessive genotypes at the E3 and E4 loci, namely e3e3e4e4 [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…is a typical short-day plant, requiring short days for the induction of flowering; therefore, identifying genetic differences in flowering conditioned by photoperiod is necessary to modify flowering time and extend the soybean growing range (Watanabe et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This wide adaptability is most likely associated with the genetic diversity of the plant (Liu et al, 2008(Liu et al, , 2009 cultivars. These mutations may represent an important source of genes for the development of soybean cultivars adapted to different low-latitude regions or sowing periods in breeding programs (Thakare et al, 2010;Watanabe et al, 2012). The genetic control of flowering time under short-day conditions is determined by a genetic system that is different and independent from the one that determines flowering under long-day conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation